Realising evidence-based software engineering a report from the workshop held at ICSE 2005. - Budgen, David (Software engineering notes.)
Context: The workshop was held to explore the potential for adapting the ideas of evidence-based practices as used in medicine and other disciplines for use in software engineering.Objectives: To devise ways of developing suitable evidence-based practices and procedures, especially the use of structured literature reviews, and introducing these into software engineering research and practice.Method: Three sessions were dedicated to a mix of presentations based on position papers and interactive discussion, while the fourth focused upon the key issues as decided by the participants.Results: An initial scoping of the major issues, identification of useful parallels, and some plans for future development of an evidence-based software engineering community.Conclusions: While there are substantial challenges to introducing evidence-based practices, there are useful experiences to be drawn from a variety of other domains.